THEORY OF PLANNED BEHAVIOR ANALYSIS OF MANUFACTURER'S INTEREST IN DOING HALAL LABELIZATION IN SHARIA ECONOMIC PERSPECTIVE (CASE STUDY OF SALT FARMING BUSINESS IN NORTH ACEH DISTRICT) - Fuadi; Falahuddin; Nazli Hasan; Futia Liza (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2022)
This study aims to determine the interest of salt farmers in doing halal labeling on their business and on their products. This study uses primary data obtained by distributing questionnaires to 26 respondents. The data analysis method used is multiple linear regression with the SPSS 20 application.The results indicate partially that Attitude (X1) positively and significantly influences producers' interest in halal labeling in Bluka Teubai Village, Dewantara subdistrict, North Aceh Regency, and Subjective Norms (X2) positively and significantly influences producers' interest in halal labeling in Bluka Teubai Village, Dewantara subdistrict, North Aceh Regency, and Behavioral Control (X3) positively and significantly influences producers' interest in halal labeling in Bluka Teubai Village, Dewantara subdistrict, North Aceh Regency with the adjusted R square (R2) value of 50.6%, and the remaining 49.4% is influenced by other variables outside this study.